Development of ergonomic work analysis when prescribed work is not clear: the case of a food industry - Losekan, Ingrid (2019)
Ergonomics has been gaining strong attention for its importance, helping to understand and act in the gap between prescribed and real work. In Brazil, a five-step Ergonomic Task Analysis (ETA) model was disseminated, namely, demand analysis, task analysis, activity analysis, diagnosis and ergonomic recommendations, although not always the distinction between the prescribed and real work is clear. In this context, the present work aims to demonstrate the implementation of an ETA in a medium-sized company that operates in the production of rice flakes and cereals in southern Brazil, in a context where the separation between the prescribed and real work is unclear. To this end, it explores the ways of implementation an ETA, from the identification of demand to the implementation of improvements, presenting at the end a critical view from the experience in the presented scenario. The results allowed us to identify that ETA can bring important opportunities if implemented longitudinally and with the proper care of observation, dialogue and analysis of operations, although there is no clear boundary between prescribed and actual work.